Phytochemical profiling and antioxidant potential of aqueous and ethereal extracts of elephants’ feeds in the savannah ecological zone of Ghana - Aguree, Sylvenus; Abagale, Samson Abah; Sackey, Isaac (International Journal of Advanced Chemistry, 2024)
This study reports on the phytochemical profiles and antioxidant properties of aqueous and ethereal crude extracts of Cassia sieberiena root, Ficus platyphylla stembark, Terminalia laxiflora root, and leaves, Tamarindus indica fruits, Kigelia africana root and Mitragyna inermis stembark as Elephants feed. Standard and approved methods were employed in this study. The phytochemical constituents detected included alkaloids, saponins, anthraquinones, tannins, flavonoids, phenols, terpenoids, and triterpenoids. The IC50s were 115 µg/mL and 7865 µg/mL for aqueous and ethereal extracts of Mitragyna inermis. 77.29 µg/mL and 1564 µg/mL for aqueous and ethereal extracts of Ficus platyphylla, 5352 µg/mL and 7843 µg/mL for aqueous and ethereal extracts of Terminalia Laxiflora, 8.963 µg/mL and 1253 µg/mL for aqueous and ethereal extracts of Cassia sieberiena, 10423µg/mL and 12645 µg/mL for aqueous and ethereal extracts of Kigelia africana, 1339 µg/mL and 2653µg/mL for aqueous and ethereal extracts of Tamarindus indica and 3.819 µg/mL for gallic acid (control). Cassia sieberiena root aqueous extract had the highest total phenol content of 62.36 ± 6.18 with a corresponding total antioxidant capacity of 289.0 ± 6.642 and the lowest total phenol content of 1.543±2.76 was detected in ethereal extract of Terminalia laxiflora leaves with a corresponding total antioxidant capacity of 241.3±4.04. The aqueous extracts possess stronger DPPH scavenging abilities compared to the ethereal extracts for all samples studied. These findings revealed the health-supporting potentials of these elephant feeds. The finding is also a guide to the managers of our zoos and National parks on the importance of natural feeding in wildlife.